MODAL SOSIAL DALAM KESIAPSIAGAAN BENCANA ERUPSI GUNUNG MERAPI DI KALURAHAN ARGOMULYO KECAMATAN CANGKRINGAN - Nanda Kusumaningsih; Retno Sunu Astuti; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2023)
One of the efforts to reduce the risk of the dangers of Mount Merapi is to make policies related to relocation. Relocation must be carried out for people who are included in the Disaster Prone Area (KRB) III of Mount Merapi. However, there are still three hamlets in KRB III Merapi that do not want to be relocated, namely Kalitengah Lor, Kalitengah Kidul and Srunen hamlets in Glagaharjo village Cangkringan district. The community's refusal to relocate will have a negative impact because Mount Merapi has a high potential for danger. Disaster preparedness management is needed by paying attention to social capital in the community. So that it can strengthen internal factors in society in facing the dangers of Merapi. This study used a qualitative method using purposive sampling in determining the subject. The techniques used for data collection are interviews, observation, and documentation on primary and secondary data. Then analyzed with an interactive model, namely data reduction, data presentation and conclusions. The results of the study found that there is social capital in the form of trust, norms and social networks. These three things make the people on the slopes of Mount Merapi more resilient and ready to face the disaster of the eruption of Mount Merapi that will occur. While habitual factors, individual roles, education and socio-economic class are the driving factors. It is recommended to expand the network, especially to private parties and agencies related to livestock rescue and care.